Theory, Praxis and the Primacy of the Object: Some Remarks on Adorno’s Conception of Dialectics - Vitali, Rolando (Scenari, 2021)
For Adorno, the possibility of a freed praxis is linked with the possibility of a freed experience. The aim of this contribution is to clarify this relationship: to do so, first I will consider the dialectical relationship between transcendental and empirical subjectivity within the framework of the Kantian epistemological foundation, showing how this foundation impedes the possibility of a freed praxis. This will clarify in what sense, for Adorno, spontaneous activity and free praxis radically diverge: for him real praxis means indeed to express the «neediness of the object» rather than the one of the subject. Finally, I will consider the relation between the essayistic form, the artwork and the theoretical activity in Adorno as an attempt to overcome the contradiction of the presupposition of a freed praxis in our society.